REKONSTRUKSI PENAFSIRAN AYAT BIDADARI SURGA MELALUI TAFSIR MUBĀDALAH - Tsania Nadzifah Hilmie; Umar Faruq Thohir (Institut Agama Islam Negeri (IAIN) Ponorogo, 2023)
One of the fundamental teachings in Islam is al-musāwah which views that all humans are equal. However, strict gender regulations in Arabic make Islamic texts described in a masculine manner and appear discriminatory against women. This raises demands to review and reinterpret religious texts. For example, religious texts about heaven, which are explained more as a vehicle for the peak of satisfaction and enjoyment for men, are not followed by adequate explanations about pleasures for women. Although no one knows exactly how the conditions in heaven will be except Allah SWT. Existing interpretations do not address women as whole human beings. Meanwhile, explanations of the existing interpretations still depart from the imagination of men. Therefore, it is important to interpret the verses of heaven with a mubādalah interpretation approach. The approach used in this library research is a philosophical approach by exploring verses that explain about verses of heavenly angels. Once collected, the data is then processed in a descriptive-analytical manner which is then analyzed using content analysis. The results of the research show that the Qirā'ah Mubādalah book was written to fight for women's rights by emphasizing the perspective of balance relations and mutuality. The construction of the mubādalah interpretation method has a concept that is oriented towards being separate from religious texts that talk about gender issues, both the Qur'an and hadith. The interpretation of the verses of the angels of heaven with the mubādalah interpretation approach becomes an offer and affirmation so that awareness regarding the position of women as the subject of the verse does not stop at the orders of faith alone, but continues on to descriptions of the rewards in heaven, so that heaven is also a place for women to get all perfect pleasure like a man.